Evaluation and Antibacterial Activity Test of Peel-off Mask Preparation from Combination of Pegagan Leaves (Centella asiatica (L) Urb.) and Charcoal Powder - Utari, Fadhilla Dwi; Hilaliyati, Najmi; Afriani, Tika (Biology, Medicine, & Natural Product Chemistry, 2024)
Pegagan leaf (Centella asiatica (L) Urb.) is a plant that contains flavonoids, tannins, triterpenoids, and saponins that function as antibacterials. Pegagan leaf is combined with activated charcoal powder, which has the job of absorbing facial oil, so that it is formulated in the form of a peel off mask to produce a synergistic effect. This study aims to formulate, evaluate, and test the antibacterial effectiveness of the peel-off mask preparation of pegagan leaf extract at concentrations of 1.5%, 2%, and 2.5%. This study uses an experimental method by testing the parameters of the physical evaluation requirements and testing antibacterial activity with the disc method on the peel off mask preparation. The results were evaluated for 28 days, and the results of the organoleptic test were stable, homogeneity stable, pH (5.6–6.2), dry time (16–25 minutes), dispersion (6.1-6.4 cm), and irritation (2 respondents). The effectiveness test against the bacteria Propionibacterium acnes has inhibitory power of 12.3 mm in the strong category. So, it can be concluded that the peel off mask produced has stable physical characteristics and can be used as an antibacterial mask.